Impact of gene modification of phosphotransferase system on expression of glutamate dehydrogenase protein of Streptococcus suis in Escherichia coli. Issue 3 (4th May 2017) - Cheng, Likun; Yang, Xiuyan; Li, Shuguang; Fu, Qiang; Fu, Shijun; Wang, Jinliang; Li, Feng; Lei, Liancheng; Shen, Zhiqiang
ABSTRACT: Glutamate dehydrogenase (GDH) protein of Streptococcus suis can be used for detection of S. suis infection and protection of pigs against S. suis infection. Acetate is a primary inhibitory metabolite for cell growth and formation of GDH protein. In this study, the ptsG gene, which encodes the integral membrane permease IICB Glc in the phosphotransferase system, was deleted and the effect of this deletion on the expression of GDH protein was investigated. The plasmids containing glfZ . mobilis (encoding glucose facilitator)– glkE . coli (encoding glucokinase) or galPE . coli (encoding galactose permease)– glkE . coli were transformed into ptsG mutant cells to recover the cell growth and glucose utilization of ptsG mutant. The mutants with deletion of ptsG decreased the accumulation of acetate; and higher cell density and GDH protein concentration were obtained with the ptsG mutants containing glf – glk or galP – glk . When the ptsG mutant containing glf – glk (SSGGFK) was used for expression of GDH protein, the cell density (optical density OD600 of 2.68) and the concentration of GDH protein (42.34 mg/L) were highest, with an increase by 12.61% and 14.84%, respectively, compared with the parental strain (SSG). The acetate accumulation was reduced to 2.35 g/L, i.e. a 37.33% decrease compared with the SSG strain. High concentration of GDH protein was obtained with reduction of acetate accumulation through gene modification of the phosphotransferase system. This can decrease the production cost of the subunit vaccine of GDH protein and provide theoretical foundation for high-level expression of other recombinant proteins.